Profile of consumers of Fortaleza agroecological fairs (Research, Society and Development, 2022)
Objective: To characterize the profile of consumers at three agroecological fairs in the city of Fortaleza-CE. Methods: This is a cross-sectional, quantitative and descriptive study. The survey was conducted with consumers while shopping at three fairs. Results: There is a predominance of consumers aged between 30 and 59 years (54.7%), mostly female (70.7%), complete higher education level (54.7%) and income greater than or equal to 5 minimum wages (44.0%). Respondents consider their health status to be good (52.0%), do not have high blood pressure (84.0%), diabetes (97.3%) and do not use medication (97.3%). As for the elevation of blood cholesterol, 82.7% reported not having it. Regarding knowledge about organic foods, indications from friends prevailed (60.0%), the reason for consumption was that it is good for health (68.0%), most have consumed organic foods for more than 6 years (32.0 %), the difficulty of consumption is the few selling places (36.0%), which is an important factor for consumption (29.3%), where most people shop at least once a week (72.0 %). The results regarding the frequency of weekly food consumption in the last month showed that respondents consume raw salad (96.0%), cooked vegetables (91.1%), fruits (88.0%), beans (88.0%), milk (56.0%), chocolate (66.7%), on five or more days a week. Conclusion: It was possible to verify the loyalty of most consumers, predominantly females, who consider their health status to be good, where a large number reported having no comorbidity, maintaining a good pattern of consumption of fruits and vegetables.